Report of the Expert Group on Programmes for Alleviation of Poverty - Planning Commission (Planning Commission Government of India, 1982)
The Expert Group on Programmes for Alleviation of Poverty, established under India’s Sixth Five-Year Plan, evaluated strategies to reduce poverty and unemployment while enhancing the quality of life for disadvantaged populations. The report emphasizes integrated rural development through initiatives such as the Integrated Rural Development Programme (IRDP), National Rural Employment Programme (NREP), and Training of Rural Youth for Self-Employment (TRYSEM). Key recommendations include strengthening decentralized planning via Panchayati Raj institutions, enhancing coordination between government schemes and voluntary organizations, targeting vulnerable communities including Scheduled Castes and Scheduled Tribes, and promoting skill development and employment generation. The report also highlights the role of educational and research institutions in designing innovative interventions, linking academic knowledge with practical rural development. By implementing these multidimensional strategies, the Expert Group envisions a systematic approach to poverty alleviation, promoting social equity, economic empowerment, and long-term sustainability for rural populations.
Planning Commission Govt. of India February 1982
Keywords: Poverty Alleviation; Sixth Five-Year Plan; Rural Development; Integrated Rural Development Programme; National Rural Employment Programme; Scheduled Castes; Scheduled Tribes; Voluntary Organizations; District Rural Development Agencies; Skill Development; Decentralized Planning; Food Security